Poly[diaqua(μ-oxalato)(μ-2-oxidopyridinium-3-carboxylato)praseodymium(III)] - Xu, Yong-Jun (International Union of Crystallography, 2009)
In the title complex, [Pr(C(6)H(4)NO(3))(C(2)O(4))(H(2)O)(2)](n), each Pr(III) ion is coordinated by eight O atoms from two 2-oxynicotinate ligands, two oxalate ligands and two water molecules, displaying a distorted bicapped square-antiprismatic geometry. The carboxylate groups link adjacent praseodymium metal centres, forming layers parallel to the bc plane. The crystal packing is stabilized by intermolecular O—H⋯O and N—H⋯O hydrogen bonds.